2022
DOI: 10.3389/fendo.2022.873508
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preservation for Adolescent and Young Adult Transmen: A Case Series and Insights on Oocyte Cryopreservation

Abstract: BackgroundThe opportunity for fertility preservation in adolescent and young adult (AYA) transmen is growing. Many AYA transmen desire future biologic children and are interested in ways to preserve fertility through oocyte cryopreservation prior to full gender affirmation, yet utilization of oocyte cryopreservation remains low. Additionally, standard practice guidelines currently do not exist for the provision of oocyte cryopreservation to AYA transmen. Our objective was to review our experience with oocyte c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Another notably young patient ≤ 12 years-old (their exact age was not specified) was a transgender male who had 9 mature oocytes cryopreserved over 2 cycles ( 29 ). A further 31 patients aged 13-15 years old ( 10 , 19 , 26 29 , 31 , 32 , 35 , 36 , 38 40 ) cryopreserved a median of 9.5 oocytes (range 0-22) and 31 patients aged 16-18 years old ( 19 , 23 25 , 27 29 , 33 , 34 , 37 , 39 ) cryopreserved a median of 14 oocytes (range 0-35).…”
Section: Resultsmentioning
confidence: 99%
“…Another notably young patient ≤ 12 years-old (their exact age was not specified) was a transgender male who had 9 mature oocytes cryopreserved over 2 cycles ( 29 ). A further 31 patients aged 13-15 years old ( 10 , 19 , 26 29 , 31 , 32 , 35 , 36 , 38 40 ) cryopreserved a median of 9.5 oocytes (range 0-22) and 31 patients aged 16-18 years old ( 19 , 23 25 , 27 29 , 33 , 34 , 37 , 39 ) cryopreserved a median of 14 oocytes (range 0-35).…”
Section: Resultsmentioning
confidence: 99%
“…The GnRHas have an impact on gamete maturation but do not cause permanent damage to gonadal function, so an interruption of testosterone can result in the recovery of ovarian function. However, the long-term effects of therapy are not known, so it is recommended to do FP before therapy Light et al 2014 [ 63 ] Duncan et al 2017 [ 67 ] Maxwell et al 2017 [ 65 ] Rothenberg et al 2019 [ 66 ] Amir et al 2020a [ 68 ] Amir et al 2020b [ 70 ] Armuand et al 2020 [ 62 ] Marschalek et al 2020 [ 69 ] Barrett et al 2022 [ 64 ] Adeleye et al 2019 [ 61 ] Semen cryopreservation Semen cryopreservation is the method of FP for young transgender women. GAHT can cause alteration of seminal sperm parameters.…”
Section: Resultsmentioning
confidence: 99%
“…In a cross-sectional study on transgender men seeking pregnancy, 88% used their own cryopreserved oocytes before hormonal transition after the age of 17 [ 63 ]. A very recent case series from a single fertility centre of 44 adolescent transgender men reported that the majority were testosterone-naive (71%, 25/35), and had not pursued gender-affirming surgery (86%, 30/35), 57% underwent oocyte cryopreservation with a median of 22 oocytes retrieved and 15 mature oocytes cryopreserved [ 64 ]. In a case-report of three transgender men undergoing oocyte cryopreservation before transition, one of them cryopreserved during adolescence: a total of 21 oocytes were retrieved and 17 mature oocytes were successfully cryopreserved with vitrification [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several of these focused on TG men who chose to complete oocyte cryopreservation before initiating testosterone therapy ( 20 , 21 , 22 ). Other studies evaluated outcomes for TG patients with prior use of exogenous testosterone therapy ( 23 , 24 , 25 , 26 , 27 ). In particular, a 2019 study by Leung et al.…”
Section: Discussionmentioning
confidence: 99%